HUBUNGAN TINGKAT STRESS KERJA PERAWAT DENGAN PELAKSANAAN SURGICAL SAFETY CHECKLIST DIKAMAR OPERASI - Taufan Arif (Jurnal Ilmiah Kesehatan Media Husada, 2021)
Introduction: Nurse work stress is a condition where nurses are faced with work demands that can result in physiological, psychological & behavioral disorders and can affect performance. The purpose of this study was to determine the relationship of nurses work stress levels with the implementation of Surgical Safety Checklist in the operating room. Methods: This research method uses correlational with cross-sectional approach and 18 respondents with a sampling technique using the entire population. The independent variable in this study is the level of work stress nurses with the dependent variable implementation of the Surgical Safety Checklist. The research instrument used a questionnaire on nurses' work stress levels and the Surgical Safety Checklist observation sheet. Scatterplot analysis results obtained negative direction which means that the increase in the variable level of work stress nurses will be followed by a decrease in the implementation of the Surgical Safety Checklist. Result: The results of the correlation coefficient 0.637 with strong interpretation and t count 3.24 more than the results of t table 1.76 means that there is a linear relationship of. Conclussion: There are relationship of nurses work stress levels with the implementation of Surgical Safety Checklist in the operating room. Discussion for the results of research where the increasing level of work stress nurses, the implementation of the Surgical Safety Checklist decrease. The recommendation for further research is to conduct research into work stress factors for nurses with the impact that can result from work stress with a higher number of respondents